Transporter-Mediated Delivery of Small Molecule Drugs to the Brain: A Critical Mechanism That Can Advance Therapeutic Development for Ischemic Stroke - Erica I. Williams; Robert D. Betterton; Thomas P. Davis; Patrick T. Ronaldson (Pharmaceutics, 2020)
Ischemic stroke is the 5th leading cause of death in the United States. Despite significant improvements in reperfusion therapies, stroke patients still suffer from debilitating neurocognitive deficits. This indicates an essential need to develop novel stroke treatment paradigms. Endogenous uptake transporters expressed at the blood-brain barrier (BBB) provide an excellent opportunity to advance stroke therapy via optimization of small molecule neuroprotective drug delivery to the brain. Examples of such uptake transporters include organic anion transporting polypeptides (OATPs in humans; Oatps in rodents) and organic cation transporters (OCTs in humans; Octs in rodents). Of particular note, small molecule drugs that have neuroprotective properties are known substrates for these transporters and include 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (i.e., statins) for OATPs/Oatps and 1-amino-3,5-dimethyladamantane (i.e., memantine) for OCTs/Octs. Here, we review current knowledge on specific BBB transporters that can be targeted for improvement of ischemic stroke treatment and provide state-of-the-art perspectives on the rationale for considering BBB transport properties during discovery/development of stroke therapeutics.